Effect of Disturbances of Zinc and Copper on the Physical and Mental Health Status of Patients with Alcohol Dependence - M. Ordak; E. Bulska; K. Jablonka-Salach; A. Luciuk; M. Maj-Żurawska; H. Matsumoto; T. Nasierowski; M. Wojnar; J. Matras; E. Muszynska; M. Bujalska-Zadrozny (Biological Trace Element Research, 2018)

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA) - S M Bergmann; Q Wang; W Zeng; Y Li; Y Wang; M Matras; M Reichert; D Fichtner; M Lenk; T Morin; N J Olesen; H F Skall; et al. (Journal of Fish Diseases, 2017)
Koi herpesvirus ( KHV ) causes KHV disease ( KHVD ). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti‐ KHV antibodies have not yet been fully validated for KHV . Therefore, it was developed and validated an enzyme‐linked immunosorbent assay ( ELISA ) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay conditions. It demonstrated high diagnostic and analytical sensitivity and specificity and was particularly useful at the pond or farm levels. Considering the scale of the carp and koi industry worldwide, this assay represents an important practical tool for the indirect detection of KHV , also in the absence of clinical signs.

Validation of a serum neutralization test for detection of antibodies specific to cyprinid herpesvirus 3 in infected common and koi carp ( Cyprinus carpio) - J Cabon; L Louboutin; J Castric; S Bergmann; G Bovo; M Matras; O Haenen; N J Olesen; T Morin (Journal of Fish Diseases, 2017)
Cyprinid herpesvirus 3 (Cy HV ‐3) is the aetiological agent of a serious infective, notifiable disease affecting common carp and varieties. In survivors, infection is generally characterized by a subclinical latency phase with restricted viral replication. The Cy HV ‐3 genome is difficult to detect in such carrier fish that represent a potential source of dissemination if viral reactivation occurs. In this study, the analytical and diagnostic performance of an alternative serum neutralization ( SN ) method based on the detection of Cy HV ‐3‐specific antibodies was assessed using 151 serum or plasma samples from healthy and naturally or experimentally Cy HV ‐3‐infected carp. French Cy HV ‐3 isolate 07/108b was neutralized efficiently by sera from carp infected with European, American and Taiwanese Cy HV ‐3 isolates, but no neutralization was observed using sera specific to other aquatic herpesviruses. Diagnostic sensitivity, diagnostic specificity and repeatability of 95.9%, 99.0% and 99.3%, respectively, were obtained, as well as a compliance rate of 89.9% in reproducibility testing. Neutralizing antibodies were steadily detected in infected carp subjected to restrictive or permissive temperature variations over more than 25 months post‐infection. The results suggest that this non‐lethal diagnostic test could be used in the future to improve the epidemiological surveillance and control of Cy HV ‐3 disease.

Carp edema virus in Polish aquaculture – evidence of significant sequence divergence and a new lineage in common carp Cyprinus carpio (L.) - M Matras; E Borzym; D Stone; K Way; M Stachnik; J Maj‐Paluch; M Palusińska; M Reichert (Journal of Fish Diseases, 2017)
Fish samples initially collected by local veterinarians on the common and koi carp farms in Poland between 2013 and 2015 as part of a KHV surveillance programme, when the water temperature was between 16 and 26 °C, and were also tested for CEV by qPCR . A partial 478 nucleotide fragment of the 4a gene was subsequently generated from 17 qPCR ‐positive common carp Cyprinus carpio samples from 36 farm sites tested during the period. Sequence alignments and analysis revealed the presence of CEV in Poland both in common carp as well as in koi carp farms, and phylogenetic analysis assigned the Polish CEV sequences into three distinct genogroups. A lineage which includes the original sequences obtained from koi carp in Japan (genogroup II ) included sequences from both koi carp and common carp, and the second lineage (genogroup I) contained sequences from common carp only. A third lineage (genogroup III ) which was more closely related to the genogroup II also consisted of sequences from common carp only. The latter represents a lineage of CEV not previously described in the literature.

Genetic diversity of spring viraemia of carp virus isolates based on the glycoprotein gene - J Maj‐Paluch; E Borzym; M Matras; M Stachnik; M Reichert (Journal of Fish Diseases, 2016)

Down‐regulation of MHC class I mRNA expression in the course of KHV infection - M Reichert; E Borzym; M Matras; J Maj‐Paluch; M Stachnik; M Palusinska (Journal of Fish Diseases, 2016)

First isolation of hirame rhabdovirus from freshwater fish in E urope - E Borzym; M Matras; J Maj‐Paluch; M Baud; C De Boisséson; C Talbi; N J Olesen; L Bigarré (Journal of Fish Diseases, 2014)
A rhabdovirus was isolated in cell culture inoculated with tissue material from diseased grayling, T hymallus thymallus (L.), originating from a fish farm affected by a mortality episode in P oland. Diagnostics tests showed that the virus was not related to novirhabdoviruses known in E urope, nor to vesiculovirus‐like species, except p erch rhabdovirus ( PR hV) with which it shared moderate serological relations. However, RT ‐ PCR with PR hV probes gave negative results. To identify the virus, a random‐priming sequence‐independent single primer amplification was adopted. Surprisingly, two of the obtained sequences exhibited a high identity (>99%) with h irame rhabdovirus ( HIRRV ), a novirhabdovirus usually found in fish in marine A siatic countries, for instance J apan, C hina and K orea. The full‐length sequence of the phosphoprotein gene (P) demonstrated a higher identity of the present isolate with HIRRV from C hina compared with the K orean isolate. An identical viral sequence was also found in brown trout, S almo trutta trutta L., affected by mortalities in a second farm in the same region, after a likely contamination from the grayling farm. To our knowledge, this is the first report of HIRRV in E urope, and in two hosts from fresh water that have not been described before as susceptible species.

Trade practices are main factors involved in the transmission of viral haemorrhagic septicaemia - M Reichert; M Matras; H F Skall; N J Olesen; S Kahns (Journal of Fish Diseases, 2013)
Viral haemorrhagic septicaemia ( VHS ), caused by the novirhabdovirus viral haemorrhagic septicaemia virus ( VHSV ), causes significant economic problems to European rainbow trout, O ncorhynchus mykiss ( W albaum), production. The virus isolates can be divided into four distinct genotypes with additional subgroups. The main source of outbreaks in European rainbow trout farming is sublineage Ia isolates. Recently, this group of isolates has been further subdivided in to two subclades of which the I a‐2 consists of isolates occurring mainly in C ontinental E urope outside of D enmark. In this study, we sequenced the full‐length G ‐gene sequences of 24 VHSV isolates that caused VHS outbreaks in P olish trout farms between 2005 and 2009. All these isolates were identified as genotype I a‐2; they divided however into two genetically distinct subgroups, that we name P ol I and P ol II . The P ol I isolates mainly caused outbreaks in the southern part of P oland, while P ol II isolates predominantly were sampled in the north of P oland, although it seems that they have been transmitted to other parts of the country. Molecular epidemiology was used for characterization of transmission pathways. This study shows that a main cause of virus transmission appears to be movement of fish. At least in P olish circumstances trading practices appear to have significant impact on spreading of VHSV infection.